6v+4-3(-6v-2)=6(v-1)

Simple and best practice solution for 6v+4-3(-6v-2)=6(v-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6v+4-3(-6v-2)=6(v-1) equation:



6v+4-3(-6v-2)=6(v-1)
We move all terms to the left:
6v+4-3(-6v-2)-(6(v-1))=0
We multiply parentheses
6v+18v-(6(v-1))+6+4=0
We calculate terms in parentheses: -(6(v-1)), so:
6(v-1)
We multiply parentheses
6v-6
Back to the equation:
-(6v-6)
We add all the numbers together, and all the variables
24v-(6v-6)+10=0
We get rid of parentheses
24v-6v+6+10=0
We add all the numbers together, and all the variables
18v+16=0
We move all terms containing v to the left, all other terms to the right
18v=-16
v=-16/18
v=-8/9

See similar equations:

| 41.66=8g+3.58 | | 21x-13=29 | | 2x-12+9x=-56 | | 5z+16=6-5z | | 45x+3=14x+30 | | 3.5(n+5)=30 | | |8x+1|=23 | | 7c-5=6c-9 | | 3/5w-1/3=-1/4 | | (x+25)+(2x+18)=(x2+3) | | 2.6y-6+0.1y=9 | | 3.5(n+5)−8=22 | | 1/4(7x-16)=3 | | x=6+3/8 | | x-6÷3=6 | | 4y-4+2(4y+1)=4(y+4) | | -2(7b+8)=8-8b | | -5x-7(-7-4x)=2(3x-4) | | 4(2x-6)=27 | | 4.6-4x=-22 | | g=4+0.93/3 | | 4(w+8)=7+4w | | -4(u-8)=-6u+22 | | 16.57=3g+3.64 | | 31-2(6x-50)=47 | | 6(x-7=10(x+4) | | 3(x-16)=56 | | b(b-3)=10 | | 2(4x)+2(3x+2)=116 | | 8x-(2x+8)=8x-20 | | 8x+11+14x-1=0 | | -2(8v-9)+2v=4(v+4) |

Equations solver categories